2016
DOI: 10.18632/oncotarget.10192
|View full text |Cite
|
Sign up to set email alerts
|

ST6Gal-I modulates docetaxel sensitivity in human hepatocarcinoma cells via the p38 MAPK/caspase pathway

Abstract: The β-galactoside α2-6-sialyltransferase 1 (ST6Gal-I) is the principal sialyltransferase responsible for the addition of α2-6-sialic acid to the termini N-glycans on cell surface. Although ST6Gal-I in cancer cell resistance to chemotherapeutics agents has been previously reported, the role of ST6Gal-I in clinical drug resistance of hepatocellular carcinoma (HCC) is not fully understood. In this study, we found that knockdown of ST6Gal-I increased the sensitivity of hepatocarcinoma MHCC97-H cells to docetaxel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…P38 likely mediates podocyte injury by triggering apoptosis and F‐actin reorganization. p38 activation has been shown in many previous studies to be strongly correlated with increases in the expression levels of the apoptosis‐related proteins Bax and cleaved caspase‐3 . In this study, p38 inhibition reduced siPlectin‐induced podocyte apoptosis and decreased Bax and cleaved caspase‐3 expression, findings that are consistent with those of prior studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…P38 likely mediates podocyte injury by triggering apoptosis and F‐actin reorganization. p38 activation has been shown in many previous studies to be strongly correlated with increases in the expression levels of the apoptosis‐related proteins Bax and cleaved caspase‐3 . In this study, p38 inhibition reduced siPlectin‐induced podocyte apoptosis and decreased Bax and cleaved caspase‐3 expression, findings that are consistent with those of prior studies.…”
Section: Discussionsupporting
confidence: 92%
“…p38 activation has been shown in many previous studies to be strongly correlated with increases in the expression levels of the apoptosis-related proteins Bax and cleaved caspase-3. 54,55 In this study, p38 inhibition reduced siPlectin-induced podocyte apoptosis and decreased Bax and cleaved caspase-3 expression, findings that are consistent with those of prior studies. Previous studies have also shown that p38 activation inhibits actin polymerization and decreases F-actin levels to maintain a dynamic and balanced F-actin cytoskeleton and normal podocyte foot process structures.…”
Section: Moreover the Expression Levels Of The Podocyte Apoptosis Masupporting
confidence: 92%
“…ST6Gal-I regulates tumor cell phenotype by modulating the sialylation, and therefore function, of key receptors that drive malignant cell behaviors [11][12][13][14][15][16][17]. We and others have shown that ST6Gal-I activity confers all of the hallmark features of a CSC including increased expression of canonical CSC markers [18], invasive potential [16,19], tumor-initiating potential [9,20], and resistance to hypoxia, chemotherapeutics, and radiation [14,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies suggest that a central cornerstone of ST6Gal-I's pro-tumorigenic function is its role in conferring a CSC phenotype (18). ST6Gal-I expression correlates with established CSC markers such ALDH1 and CD133 (19), and ST6Gal-I activity imparts hallmark CSC characteristics, including tumor spheroid growth, cell invasiveness, tumor-initiating potential, and resistance to cytotoxic stimuli, including chemotherapeutic drugs (18,(23)(24)(25)(26)(27)(28)(29)(30)(31). ST6Gal-I also promotes epithelial-to-mesenchymal transition (32).…”
mentioning
confidence: 99%